Druggable protein prediction using a multi-canal deep convolutional neural network based on autocovariance method. (December 2022) - Iraji, Mohammad Saber; Tanha, Jafar; Habibinejad, Mahboobeh
Abstract: Drug targets must be identified and positioned correctly to research and manufacture new drugs. In this study, rather than using traditional methods for drug expansion, the drug target is determined using machine learning. Machine learning has generated significant interest and desire in recent years and extensive research due to its low cost and speed of operation. As a result, it is critical to develop an intelligent classification system for drug proteins. This study proposes two distinct models for the prediction of druggable protein classes based on the deep learning method. The translation of drug-protein sequences is based on six physicochemical properties of amino acids. Following the application of the autocovariance method, converted sequences are used as fixed-length input vectors in deep stacked sparse auto-encoders (DSSAEs) network. The coded protein sequences are also considered and utilized as a six-channel input vector for the deep convolutional neural network model. The experimental results contributing to the deep convolution model are more efficient than previous studies for classifying druggable proteins. The proposed approach achieved a sensitivity of 96.92%, a specificity of 99.51%, and an accuracy of 98.29%. Highlights: This study proposes two distinct models for predicting druggable protein classes. Drug-protein sequences are translated based on six physicochemical properties of amino acids. After employing the autocovariance method, deep stacked sparse auto-encoders are utilized. A six-channel input vector is entered into the deep convolutional neural network model. The deep convolution model is more efficient for classifying druggable proteins.